Wireline log analysis of Harvey 1, South Perth Basin - Rezaee, R (Australian National Low Emission Carbon (ANLEC), 2012)
This study is part of the ANLEC R&D project to evaluate the suitability of the lower Lesueur Sandstone, in Harvey 1 of the Southern Perth Basin, to mitigate carbon dioxide (CO2) emitted by the Collie’s coal-fired power stations, Western Australia. Well log data of Harvey 1 are interpreted to obtain rock properties required for carbon capture and storage (CCS) site evaluation. A complete suite of log data was used to evaluate petrophysical properties of the Lesueur sandstone.